Low temperature dehydrations of non-activated alcohols via halide catalysis. Issue 6 (14th April 2016) - Zhang, X.; Desrochers, S. J.; Carl, A. D.; Geagea, N.; Zielinski, K.; Emmert, M. H.
Abstract : Through concurrent halide and acid catalysis, olefin-forming dehydrations and non-rearranging Friedel–Crafts alkylations under mild conditions are established. Abstract : Activating kinetically inert C–O bonds such as in primary alcohols is an important challenge for the transformation of biomass-derived feedstocks. The herein described methodology addresses this issue through a combination of halide and acid catalysis. The novel mechanistic pathway proposed based on detailed experimental studies enables selective olefin formation from alcohols – as opposed to ether formation – at relatively low temperatures. Suitable substrates are tertiary, secondary, and even primary alcohols. Furthermore, the observed selectivity for the Hoffman elimination product and the realization of a non-rearranging Friedel–Crafts alkylation suggest that the reaction medium with high concentrations of halide (NBu4 Br) enables reaction outcomes that cannot be obtained through carbocation intermediates.